Critical Success Trust Factors in e-Commerce and m-Commerce : The Case of the Business-to-Consumer (B2C) Environment in Malaysia and China - Wong, Li Fang (2015)
Developing countries will be fuelling the next wave of consumerism. E-Commerce has brought an entire new way of delivering products and services in these nations. This is because the developing countries have different cultural environment from western countries. It is becoming an attractive avenue to conduct business and consume alike. It helps in accelerating the economic growth in these nations. Trust is becoming ever more important and serves a vital success element in this virtual environment. Those organizations, business vendor, or entrepreneurs that master this will gain the competitive advantage and survive the next business wave. In this research, B2C e-Commerce channel was used to understand the role of trust in Internet transaction in Malaysia and China. The results of the existing studies on online trust may not be directly applied to Malaysia and China without actual examination. This research was inspired by trust models proposed by Salo & Karjaluoto (2007) and Chen & Saeedi (2006). The trust mechanisms and trust factors that affecting consumer’s trust and behaviour was studies and reviewed. It was found that consumer characteristics have direct influenced on consumer purchasing intentions while web merchants should have trustworthiness characteristics such as ability, integrity and benevolence. This has a significant impact on the way trust is established, maintained with consequent impact and provides insightful understanding of consumer’s online trust. According to the findings of the study, size of vendor appeared to have significant relation with establishment of initial online trust in China. The results were compared between countries, gender and age group which enable web merchants to understand more about different online consumers in order for them to build a secured and trusted e-Commerce website and m-Commerce application.